Fabrication of stabilized piezoelectric thick film for silicon-based MEMS device - Kwon, T. Y.; Kim, Y. B.; Eom, K.; Yoon, D. S.; Lee, H. L.; Kim, T. S. (SPRINGER HEIDELBERG, 2007)
Electrical properties of piezoelectric thick films with controlled microstructure were investigated. In order to enhance the electromechanical properties (e.g. d(31), d(33)) of a thick film by control of its microstructure, a mixed powder, referred to as BNP, consisting of both nano-sized and micro-sized piezoelectric particles, was employed as a starting precursor in the film fabrication process. According to a scanning electron microscopy study, it is shown that a BNP thick film exhibits the densest homogeneous microstructures. According to surface area measurements, the BNP thick film was sufficiently densified without an additional infiltration process of Pb(Zr1-xTix)O-3 sol for densification. The screen-printed BNP thick film possesses a dielectric constant and a remanent polarization much higher than those of a thick film composed of only micro-sized piezoelectric particles by a factor of more than two. This suggests the potential application of the BNP thick film, in conjunction with a silicon substrate, to a micromachined monolithic PZT thick film device on the silicon substrate.
Keywords: PZT; SENSORS; MICROCANTILEVER; STRESS